A simple, rapid method for evaluation of transfection efficiency based on fluorescent dye. Issue 3 (4th May 2017) - Peng, Lin; Xiong, Wendian; Cai, Yanfei; Chen, Yun; He, Yang; Yang, Jianfeng; Jin, Jian; Li, Huazhong
ABSTRACT: Enhanced transfection efficiency of transient gene expression (TGE) and electroporation is a useful approach for improvement of recombinant therapeutic proteins in mammalian cells. A novel method is described here in which CHO cells expressing recombinant FVII (rFVII) were labeled with fluorescent dye and analyzed by confocal microscopy. Cells with or without rFVII encoding gene were detectable by flow cytometry. Thus, we were able to distinguish positive cells (with rFVII encoding gene) and quantify their percentages. We evaluated the effects of varying electroporation conditions (voltage, number of repetitions, plasmid amount, carrier DNA) in order to optimize transfection efficiency. The highest transfection efficiency achieved was ∼86%. The method described here allows rapid evaluation of transfection efficiency without co-expression of reporter genes. In combination with appropriate antibodies, the method can be extended to evaluation of transfection efficiency in cells expressing other recombinant proteins.